Experimental and Numerical Investigation of Spray Scrubber Dust Collection Efficiency - Adam Tomaszewski; Tomasz Przybyliński; Marcin Lackowski (Applied Sciences)
Spray scrubbers are widely used in gas purification applications and allow fulfillment of the demands of air quality norms introduced all over the world. They effectively remove harmful gases like sulfur dioxide (SO2), nitrogen oxides (NOx), and particulate matter from industrial emissions, reducing their impact on air quality. Moreover, by capturing greenhouse gases such as carbon dioxide (CO2) in certain applications, spray scrubbers contribute to efforts to reduce climate change. Optimization of scrubber internal elements leads to reduced energy usage and lowered water mass flow while maintaining high pollutant removal efficiency. This makes them cost-effective in the long term. The demister is an additional device which is often used in scrubbing systems, and its main task is to prevent the water droplets from escaping through the upper part of the scrubbing chamber. In this article, the pollution (MgO particles) is introduced to the system upstream the scrubber inlet, the working fluid is air under atmospheric pressure, and water droplets are generated by a single nozzle placed inside the scrubber. Before the experimental part, a preliminary numerical analysis of gas velocity inside scrubber is performed and expectations of particle behavior are indicated. Then, the authors present the spray scrubber laboratory stand designed by them and carry out experimental research on it. Each element of the test stand is described in the article including the self-designed fluidizer, which effectively mixes MgO powder with air. The authors investigate the effect of their innovative construction of demister on separation efficiency and compare the results to the case without demister. The impact of water mass flow rate generated by the nozzle and gas inlet velocity on separation efficiency is presented for several investigated cases. The results show that demisters significantly improve the separation efficiency at lower water mass flow rates and successfully prevent water droplets from reaching the scrubber outlet. The measured separation efficiency was in the range of 80% for lower water mass flow rates up to 97% for the highest water flows.